The Efficiency of Using New Information and Communication Technologies in Primary School Lessons: the E-Learning Experience - MOIKO, Oksana; PREDYK, Аліна Анатоліївна; BAKHMAT, Nataliia; Kravchuk, Oksana; Streletska, Nataliia; Zakharova, Hanna (Postmodern Openings, 2022)
The importance of the topic of the article lies in the fact that in the era of postmodernism, informatization of the elementary school allows you to improve the quality of the educational process, through the use of information and communication technologies (ICT) to simplify management of the educational process, to organize the exchange of teaching experience, to expand didactic capabilities of the lesson. The purpose of the article is the need to study and justify the importance of using new ICT in primary school lessons, to expand the experience of e-learning in primary school. The article expands the concept of information and communication technologies and their benefits in primary school; given the rationale for conducting a lesson using ICT; the experience of e-learning in the primary school of the postmodern era is characterized. Thus, one of the priorities of the development of education in postmodern society is the professional application in all areas of information technology and e-learning, which can increase the interest of present students and improve the ability to adapt to current electronic information society. The formation of knowledge and skills in the field of computer literacy of teachers and students will be an indicator of compliance of its level with current requirements.
Keywords: Digitalization of education; present-day means in education; methods of informatization implementation; model of using new technologies; educational platforms